2017
DOI: 10.1016/j.celrep.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Global but Not Targeted Demethylation in iPSC Reprogramming

Abstract: SummaryGlobal DNA demethylation is an integral part of reprogramming processes in vivo and in vitro, but whether it occurs in the derivation of induced pluripotent stem cells (iPSCs) is not known. Here, we show that iPSC reprogramming involves both global and targeted demethylation, which are separable mechanistically and by their biological outcomes. Cells at intermediate-late stages of reprogramming undergo transient genome-wide demethylation, which is more pronounced in female cells. Global demethylation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 51 publications
10
86
0
Order By: Relevance
“…One outcome of our study is that the number of active X-chromosomes correlates with differences in the transcriptome and in pluripotency exit in iPSCs (Fig 1), in addition to differences in DNA methylation [22,23]. Reprogramming somatic cells to iPSCs is an important system to study erasure of epigenetic memory and pluripotency.…”
Section: Impact Of X-dosage On the Transcriptome And Pluripotency Eximentioning
confidence: 75%
See 2 more Smart Citations
“…One outcome of our study is that the number of active X-chromosomes correlates with differences in the transcriptome and in pluripotency exit in iPSCs (Fig 1), in addition to differences in DNA methylation [22,23]. Reprogramming somatic cells to iPSCs is an important system to study erasure of epigenetic memory and pluripotency.…”
Section: Impact Of X-dosage On the Transcriptome And Pluripotency Eximentioning
confidence: 75%
“…Work over the past decade showed that XX female ESCs exhibit global DNA hypomethylation affecting most genomic features including imprint control regions [13][14][15][16][17][18][19][20][21]. Recent work showed that XX female iPSCs also display global hypomethylation [22,23]. Differences in global DNA methylation have been attributed to X-dosage since female XO cells display male-like DNA methylation levels [13,15,17].…”
Section: Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iPSCs can differentiate into nearly all types of cells in the body. A major principle in iPSCs was the cellular reprogramming technology using various methods as somatic cell nuclear transfer, cell fusion, and currently by means of reprogramming factors, which helped to establish and maintain cellular identity during development by the stepwise activation of fundamental pluripotency genes and the silencing of somatic cell‐of‐origin genes (Ma, Xie, Laurent, & Ding, ; Milagre et al, ; Szablowska‐Gadomska, Gorska, & Malecki, ; Zhang, ). In our review, the most commonly used reprogramming factors were either Yamanaka (OSKM) or Thomson reprogramming factors (OSNL; Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Female ESCs are also karyotypically unstable, with XO cells rapidly dominating cultures (Choi et al, 2017b;Yagi et al, 2017;Zvetkova et al, 2005), which is also observed in human female embryonic stem cells (Di Stefano et al, 2018). These complications additionally arise when somatic female cells are reprogrammed to induced pluripotent stem cells (iPSCs) (Milagre et al, 2017;Pasque et al, 2018;Song et al, 2019), suggesting that these are features of female pluripotency in culture that confound both research requiring such cells and future medical applications.…”
Section: Introductionmentioning
confidence: 99%